Biting the Hand - Richard Thomas (Journalism Studies, 2019)
The Global Financial Crisis presented the media with numerous opportunities to tell dramatic business-based stories. However, the relationship between commercial news and the corporate world is often thought to be deferential, where advertisers wield influence over journalists who are reluctant to criticise those indirectly funding them. Because of these models of capitalist power dynamics, it is often assumed that journalists will take a gentle line when reporting the affairs of advertisers. However, such a normative ideal is essential in an era when evidence suggests that capitalism has not produced any “trickle-down” benefits for ordinary people. By taking a multimodal approach including semiotic and critical discourse analysis, this paper examines the broadcaster–advertiser relationship between ITV and Barclays PLC. Using a critical realist framework, the paper finds that in contrast to well-established theories that advertisers shape and influence business news, post-financial crisis, the United Kingdom’s largest commercial broadcaster adopted a combative role towards a key contributor to their funding. In comparison, the nation’s main public service broadcaster—the BBC—was less probing. The paper therefore challenges any simplistic correlation between advertising and news output while also arguing that a political economy perspective remains relevant in today’s commercial news landscape